ISOLASI DAN PENCIRIAN LIGNIN DARI LINDI HITAM DAN SENGON UNTUK BAHAN PEREKAT - Adi Santoso; Surdiding Ruhendi; Suminar S Achmadi; Endang Suhendang (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
Lignin is the polymer which has been degraded and removed in pulping processes. The occurance of lignin as a waste product in pulp mills has made it an attractive raw material for adhesives eversince the beginning of the sulfite pulping of wood. Therefore, the isolation and its characterization are important lo achieve effective lignin removal. In this investigation, isolation and characterization of black liquor and sengon lignin were carried out. the isolation of lignin was performed by precipitation of lignin from black liquor and the preparation of lignin by way of cellulose dissolution from sengon (Paraserianthes falcataria (L) Nielsen). the recovery of lignin was evaluated in an allempt to optimize recovery at high purity by qualitative analyses (ie. UV - and IR - spectrometry) and quantitative analyses (ie. percentage of pure lignin, equivalent weight, ash content, etc). lndulin-AT (commercial lignin) is used as standard of comparison.the result indicates that black liquor lignin is guayacil lignin with 16,8 - 17,4% methoxyl content, 2.0 - 2.1 % phenolic hydroxyl content, 11. 7 - 11.9% ash content and percentage of pure lignin about 64. 2 - 71.1 %. this result is similar with indulin - AT. the result of sengon lignin analyses show that it is syringyl lignin with 26.7 - 27.2% methoxyl content, 0.8 - 0.9% phenolic hidroxyl content, 25.1 - 25. 6% ash content and percentage of pure lignin about 36. 1 -46.2%. Side effect of these result were reactivity of sengon lignin is lower than lignin from black liquor and indulin - AT, therefore, sengon lignin has no potential as raw material for adhesives.